Both Positive and Negative Fluid Balance May Be Associated with Reduced Long-term Survival in the Critically Ill - Balakumar, Vikram (Crit Care Med, 2017)
OBJECTIVE: Among critically ill patients with acute kidney injury, exposure to positive fluid balance (FB), compared with negative FB, has been associated with mortality and impaired renal recovery. However, its unclear whether positive and negative FB are associated with poor outcome compared to patients with even fluid balance (euvolemia). In this study, we examined the association between exposure to positive or negative FB, compared with even FB, on one-year mortality and renal recovery. DESIGN: Retrospective cohort study. SETTING: Eight medical-surgical ICUs at the University of Pittsburgh Medical Center, Pittsburgh, PA. PATIENTS: Critically ill patients admitted between July 2000 through October 2008. INTERVENTIONS: None MEASUREMENTS & MAIN RESULTS: Among 18,084 patients, FB was categorized as negative (<0%); even (0 % – < 5%); or positive (≥5%). Following propensity matching, positive FB, compared with even or negative FB, was associated with increased mortality (30.3% vs. 21.1% vs. 22%, respectively, P<0.001). Using Gray’s model, negative compared with even FB, was associated with lower short-term mortality (adjusted hazard ratio range [AHR], 0.81, 95%CI, 0.68–0.96) but higher long-term mortality (AHR range, 1.16–1.22, P=0.004). Conversely, positive FB, was associated with higher mortality throughout one-year (AHR range, 1.30–1.92, P<0.001), which was attenuated in those who received RRT (Positive FB*RRT interaction AHR range, 0.43–0.89, P<0.001). Of patients receiving RRT, neither positive (adjusted odds ratio [AOR], 95% CI, 0.98, 0.68–1.4) nor negative (AOR, 0.81, 95% CI, 0.43–1.55) FB was associated with renal recovery. CONCLUSIONS: Among critically ill patients, exposure to positive or negative FB, compared with even FB, was associated with higher one-year mortality. This mortality risk associated with positive FB, however, was attenuated by use of RRT. We found no association between FB and renal recovery.